Chemosaturation with percutaneous hepatic perfusion of melphalan for metastatic uveal melanoma. Issue 2 (25th January 2022) - Modi, Sachin; Gibson, Tom; Vigneswaran, Ganesh; Patel, Shian; Wheater, Matthew; Karydis, Ioannis; Gupta, Sanjay; Takhar, Arjun; Pearce, Neil; Ottensmeier, Christian; Stedman, Brian
Abstract : Supplemental Digital Content is available in the text. Abstract : Uveal melanoma, the most common primary ocular malignancy in adults, carries a poor prognosis: 50% of patients develop the metastatic disease with a 10–25% 1-year survival and no established standard of care treatment. Prior studies of melphalan percutaneous hepatic perfusion (M-PHP) have shown promise in metastatic uveal melanoma (mUM) patients with liver predominant disease but are limited by small sample sizes. We contribute our findings on the safety and efficacy of the procedure in the largest sample population to date. A retrospective analysis of outcome and safety data for all mUM patients receiving M-PHP was performed. Tumour response and treatment toxicity were evaluated using RECIST 1.1 and Common Terminology Criteria for Adverse Events v5.03, respectively. 250 M-PHP procedures were performed in 81 patients (median of three per patient). The analysis demonstrated a hepatic disease control rate of 88.9% (72/81), a hepatic response rate of 66.7% (54/81), and an overall response rate of 60.5% (49/81). After a median follow-up of 12.9 months, median overall progression-free (PFS) and median overall survival (OS) were 8.4 and 14.9 months, respectively. There were no fatal treatment-related adverse events (TRAE). Forty-three grade 3 (29) or 4 (14) TRAE occurred in 23 (27.7%) patients with a significant reduction in such events between procedures performed in 2016–2020 vs. 2012–2016 (0.17 vs. 0.90 per patient, P < 0.001). M-PHP provides excellent response rates and PFS compared with other available treatments, with decreasing side effect profile with experience. Combination therapy with systemic agents may be viable to further advance OS.